Niobium addition to sol-gel derived bioactive glass powders and scaffolds: In vitro characterization and effect on pre-osteoblastic cell behavior. Issue 10 (October 2018) - Balbinot, Gabriela de Souza; Collares, Fabricio Mezzomo; Visioli, Fernanda; Soares, Priscilla Barbosa Ferreira; Takimi, Antonio Shigueaki; Samuel, Susana Maria Werner; Leitune, Vicente Castelo Braco
Graphical Abstract: Highlights: Bioactive glass scaffolds containing niobium were successfully synthesized through sol-gel foaming method. Niobium was found scattered through glass matrix. μCT analysis showed suitable macrostructure for bone regeneration. Cell behaviour was positively influenced by niobium in glass structure showing an increase in mineralization of pre-osteoblastic cells.